The Influence of Product Quality and Price on Purchasing Decisions at Indogrosir Shopping Center in Ambon - Matdoan, Istiqamah; Rehatta, Geradin; Louhenapessy, William George M (Universitas Pattimura, 2025)
This research aims to analyze the influence of product quality and price on purchasing decisions at the Indogrosir shopping centre in Ambon. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to consumers shopping at Indogrosir. Data analysis was conducted using multiple linear regression to determine the simultaneous and partial effects of product quality and price variables on purchasing decisions. The results indicate that both product quality and price simultaneously significantly affect purchasing decisions. However, price has a more dominant influence compared to product quality. Consumers are more likely to consider affordable prices that align with the expected product quality. Therefore, it is important for Indogrosir to continuously improve its pricing strategy and maintain product quality to enhance customer loyalty and competitiveness in the retail market